The expression coud be re written:
12x²y/2xy + 6xy/2xy + 4x²/2xy . Simplify numerator & denominator whenever it is possible:
6x-3+2x/y
Good evening ,
______
Answer:
No
___________________
Step-by-step explanation:
Look at the photo below for the details.
:)
Answer:
She used the addition property of equality:
p2 + 5 = 8p - 7
+7 +7
p2 + 12 = 8p
Answer:
x^2 -2xy -10y^2
x^2 -9xy +4 y^2
3x^3 +6x^2 -24 x +27
Step-by-step explanation:
3x^2-5xy -6y^2 -( 2x^2 -3xy+4y^2)
= 3x^2- 2x^2 -5xy +3xy-6y^2 -4 Y^2
= x^2 -2xy -10y^2
2x^2−5xy+y^2 -( x^2+4xy−3y^2)
=2 x^2 -x^2 -5xy -4xy +y^2 +3 y^2
=x^2 -9xy +4 y^2
7x^3−16x+18- (4x^3−6x^2+8x−9)
= 7x^3 -4x^3 + 6x^2-16x- 8x +18 +9
=3x^3 +6x^2 -24 x +27